How big business got Brazil hooked on junk food - Jacobs , Andrew; Richtel, Matt (Brazilian Journal of Implantology and Health Sciences, 2023)
The desire to kick the habit of eating junk food is shared by millions of people. Unfortunately, they didn’t realize how many billions of dollars food manufacturers have invested into figuring out exactly what the brain loves!